TLR2-Modulating Lipoproteins of the Mycobacterium tuberculosis Complex Enhance the HIV Infectivity of CD4+ T Cells. - Ciaran Skerry; Lee G Klinkenberg; Kathleen R Page; Petros C Karakousis (PLoS ONE, 2016)
Co-infection with Mycobacterium tuberculosis accelerates progression from HIV to AIDS. Our previous studies showed that M. tuberculosis complex, unlike M. smegmatis, enhances TLR2-dependent susceptibility of CD4+ T cells to HIV. The M. tuberculosis complex produces multiple TLR2-stimulating lipoproteins, which are absent in M. smegmatis. M. tuberculosis production of mature lipoproteins and TLR2 stimulation is dependent on cleavage by lipoprotein signal peptidase A (LspA). In order to determine the role of potential TLR2-stimulating lipoproteins on mycobacterial-mediated HIV infectivity of CD4+ T cells, we generated M. smegmatis recombinant strains overexpressing genes encoding various M. bovis BCG lipoproteins, as well as a Mycobacterium bovis BCG strain deficient in LspA (ΔlspA). Exposure of human peripheral blood mononuclear cells (PBMC) to M. smegmatis strains overexpressing the BCG lipoproteins, LprF (p<0.01), LprH (p<0.05), LprI (p<0.05), LprP (p<0.001), LprQ (p<0.005), MPT83 (p<0.005), or PhoS1 (p<0.05), resulted in increased HIV infectivity of CD4+ T cells isolated from these PBMC. Conversely, infection of PBMC with ΔlspA reduced HIV infectivity of CD4+ T cells by 40% relative to BCG-infected cells (p<0.05). These results may have important implications for TB vaccination programs in areas with high mother-to-child HIV transmission.